A Blockchain-based Architecture for Query and Registration of Student Degree Certificates - Abreu, Antonio Wellington S.; Coutinho, Emanuel F.; Bezerra, Carla I. M. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2020: Anais do XIV Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2020)
Blockchain is an emerging technology that has piqued the interest of researchers and industry today. Following the success of this technology in the financial market with virtual currencies, blockchain begins to be used by different domains such as government and education as it provides a reliable, scalable and unchanging distributed environment for conducting and storing transactions on a network. Higher education is a system with many challenges that could be solved by adopting this technology. Protecting data transactions that involve student degrees is one of the challenges considered by educational institutions. Thus, this paper presents a reference architecture proposal based on blockchain technology and a proof of concept to register and consult student certificates issued by higher education institutions. With this architecture, we intend to evaluate a new business model in this technology applied to the educational domain. As a proof of concept, we presented a prototype implementation using smart contracts based on the Ethereum platform and an evaluation made by experts in high education.